Polyploidization facilitates biotechnological in vitro techniques in the genus Cucumis - Skálová, Dagmar; Ondřej, Vladan; Doležalová, Ivana; Navrátilová, Božena; Lebeda, Aleš (Journal of biomedicine & biotechnology, 2010)
Prezygotic interspecific crossability barrier in the genus Cucumis is related to the ploidy level of the species (cucumber (C. sativus), x = 7; muskmelon (C. melo) and wild Cucumis species, x = 12). Polyploidization of maternal plants helps hybridization among other Cucumis species by overcoming prezygotic genetic barriers. The main objective of this paper is to compare the results of several methods supporting interspecific crosses in cucumber without and with polyploidization (comparison between diploid (2x) and mixoploid (2x/4x) cucumber maternal plants). Mixoploid plants were obtained after in vivo and in vitro polyploidization by colchicine and oryzalin. Ploidy level was estimated by flow cytometry. Embryo rescue, in vitro pollination, and isolation of mesophyll protoplast were tested and compared. Positive effect of polyploidization was observed during all experiments presented by higher regeneration capacity of cultivated mixoploid cucumber embryos, ovules, and protoplasts. Nevertheless, the hybrid character of putative hybrid accessions obtained after cross in vivo and in vitro pollination was not confirmed.
Keywords: hybridizace genetická; biotechnologie; ploidie; DNA shuffling; DNA Shuffling; Pollination; Polyploidy; druhová specificita; duplikace chromozomů; Cucumis; opylení; Chromosome Duplication; Ploidies; polyploidie; Biotechnology; Species Specificity; Hybridization, Genetic